Analisis Kebutuhan Siswa di SMA Negeri 3 Bolo Terhadap Bahan Ajar Bergambar pada Materi Plantae - Mardiana Mardiana; Muhammad Akhyar; Akhmad Arif Musada (International Consortium of Education and Culture Research Studies, 2019)
Biology lesson material is closely related to the surrounding environment. To support students to be able to learn it, the media that associates academic concepts and the surrounding environment / the real world is needed. Related to this, the study aims to analyze the needs of SMA 3 Bolo students on pictured learning materials on the discussion of Plantae. The research method used is descriptive analysis and in-depth interviews, done by using questionnaire related to the learning materials used. From the results of the study, it is known that 75% of students' answers show that SMA Bolo 3 students need pictured learning materials for biology learning especially one related to plantae to create more meaningful and enjoyable learning process. This approach can direct students to understand academic concepts and have the opportunity to be directly involved in learning as well as understand the subject matter easily as learning is presented in the form of images that are easily found in their daily lives. With this, pictured Learning materials is one of the solutions in biology learning, especially in the discussion of Plantae.